Analysis and Research on Energy-Saving Reconstruction of Building Heating System - Yongqiang Liu; Zhanfang Huang (Advances in Civil Engineering)
A building heating system had high energy consumption and did not meet the requirements of environmental protection, so it was needed to be reformed. After recalculating the heat load, it was found that the heat source, pipe network specification, and radiator area of the original heating system were oversized. After comparing with a gas-fired boiler, the heat source was transformed into the water source heat pump system. The water supply temperature of the water source heat pump was lower than that of the boiler. Generally, it seemed necessary to increase the radiator area. However, after calculation and verification, when the supply and return water temperature was 65/58°C, the system operated continuously and the original pipe network and radiator could still ensure the indoor temperature of 16°C. The total cost of transformation was 11.5 million Chinese Yuan. After analyzing the operation data of the new system, the water source heat pump system could save 82.6% energy compared with the original system and 29.6% cost compared with the central heating system. The transformation is successful, and the experience is worth popularizing.